The First Polish-German Scientific Seminar "Folk Universities - Between Theory and Practice", Uniwersytet Szczeciński, 6-7.10 2017 - Angelika Felska (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2018)
Reports